2014
DOI: 10.1007/978-3-319-02411-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy for Pseudo-occlusion of the Cervical Internal Carotid Artery

Abstract: Patients with PO had more fibrous plaques and two different histological features, including total occlusion with recanalization or severe stenosis. The plaque histology may be related to the pathogenesis and the surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Patients with CNO were then excluded from most subsequent randomized controlled trials. So only data from cohort studies evaluating CEA, CAS, or best medical treatment (BMT) were reported ( 9 , 16 18 ) and the reported results were highly heterogenous. Since the periprocedural risk for CEA decreased significantly in the past years ( 19 ), more and more investigators tried to carry out CEA for patients with CNO and achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CNO were then excluded from most subsequent randomized controlled trials. So only data from cohort studies evaluating CEA, CAS, or best medical treatment (BMT) were reported ( 9 , 16 18 ) and the reported results were highly heterogenous. Since the periprocedural risk for CEA decreased significantly in the past years ( 19 ), more and more investigators tried to carry out CEA for patients with CNO and achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…Reported outcomes were highly heterogeneous and ranged from a 30-day stroke/death risk of 0–11.1% for CEA [1113, 20] to 0–9.2% for CAS [57, 1618] and 0–43% for best medical treatment (BMT) [8, 12, 19]. Furthermore, analyses of published studies are hampered by both a variety in inclusion criteria and the reporting of different clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of cohort studies have published the results of their centers’ preferred treatment approach, which varied from CEA [ 11 13 ] to carotid artery stenting (CAS) [ 4 7 , 14 18 ] or BMT [ 8 , 12 , 19 ]. Reported outcomes were highly heterogeneous and ranged from a 30-day stroke/death risk of 0–11.1% for CEA [ 11 13 , 20 ] to 0–9.2% for CAS [ 5 7 , 16 18 ] and 0–43% for best medical treatment (BMT) [ 8 , 12 , 19 ]. Furthermore, analyses of published studies are hampered by both a variety in inclusion criteria and the reporting of different clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After applying exclusion criteria, 92 studies were excluded and finally 33 articles participated in the meta-analysis. More specifically, the literature review revealed 13 articles on CEA (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), 12 articles on CAS (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), 5 studies on BMT and CEA (37)(38)(39)(40)(41), 2 studies on CEA and CAS (42,43) and 1 study on BMT (44) (Figure 1: flow chart). The demographic characteristics of the 33 eligible studies included in our study are presented in Tables 1,2.…”
Section: Resultsmentioning
confidence: 99%